Thermal insulation, power generation, lighting and energy saving performance of heat insulation solar glass as a curtain wall application in Taiwan: A comparative experimental study. (15th May 2015) - Cuce, Erdem; Riffat, Saffa B.; Young, Chin-Huai
Highlights: Heat insulation solar glass curtain walls are compared with ordinary glass. Novel curtain walls are capable of supplying additional energy to the house. Novel curtain walls achieve a 100% ultraviolet light blocking rate. Novel curtain walls require 40.8% and 46.9% less energy for heating and cooling. Novel curtain walls achieve 24.9% better lighting performance. Abstract: Glass curtain walls are very popular in modern architecture due to their attractive aesthetic features and characteristic benefits such as efficient daylighting. However, current curtain wall systems are usually built via conventional fenestration products resulting to significantly greater heating and cooling demand in buildings compared to other construction types. In this respect, novel solutions are required to improve poor performance parameters of existing curtain walls. Therefore in this study, our previous research on heat insulation solar glass technology is extended to curtain walls. Two test houses having ordinary glass and novel glass curtain walls are constructed in Taiwan and experimentally investigated in terms of various performance parameters such as ultraviolet light penetration, thermal insulation, power generation, indoor lighting and energy saving efficiency. The results reveal that novel glass curtain walls have a 100% ultraviolet light blocking rate, which is of vital importance for occupants' health. Additionally, 95% of excessive thermal radiation is prevented from penetrating into the living space via novel glass curtain walls, yielding 40.8% and 46.9% mitigation in heating and cooling demand of buildings compared to ordinary glass curtain walls. Moreover, novel glass curtain walls have 24.9% better lighting efficiency as well as being capable of producing electricity to be used for lighting or any other purposes.